2003
DOI: 10.1007/s00468-002-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Four years of ozone exposure at high or low phosphorus reduced biomass in Norway spruce

Abstract: Saplings of one clone of Norway spruce (Picea abies) were planted in pots and exposed to charcoal filtered (CF) air, non-filtered (NF) air or NF air plus extra ozone (NF+; ambient 1.4) in open-top chambers (OTCs). The lowest and highest ozone concentrations were combined with low phosphorus (LP) supply. Ambient air plots without OTCs, and with and without pots, were also included. A long-term study was conducted with 756 trees (3-7 years old) harvested successively over four growing seasons. Ozone had a negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Between container differences were not indicated (data not shown), but limitation in space (the size of the containers was limited due to the exposure sites on the scaffolding) and specifically downward-oriented root growth were observed. Similar growth was also observed in experiments with spruce (Ottossen et al, 2003), where root growth was triggered by a gradient of water and nutrients to produce growth towards the bottom of the pots. Nutrient availability and mycorrhizal colonization (as found in our container-grown beech plants) modulate the longevity of fine roots (Pregitzer, 2003), which is critical to the overall functionality of the root system (Zobel, 2003).…”
Section: Final Discussionsupporting
confidence: 78%
“…Between container differences were not indicated (data not shown), but limitation in space (the size of the containers was limited due to the exposure sites on the scaffolding) and specifically downward-oriented root growth were observed. Similar growth was also observed in experiments with spruce (Ottossen et al, 2003), where root growth was triggered by a gradient of water and nutrients to produce growth towards the bottom of the pots. Nutrient availability and mycorrhizal colonization (as found in our container-grown beech plants) modulate the longevity of fine roots (Pregitzer, 2003), which is critical to the overall functionality of the root system (Zobel, 2003).…”
Section: Final Discussionsupporting
confidence: 78%
“…Our results are in opposition to several other studies, where a decrease in coarse, medium and fine root biomass with increased pollutant (ozone) load across a gradient (Grulke et al, 1998) was observed. A non-significant decrease of root biomass (Ottossen et al, 2003) or a quick decrease in carbon allocation to roots and subsequent within-one-growing season biomass decrease (Andersen, 2003) has been observed, although in the latter paper the number of short roots remained unaffected (Andersen, 2003). An increase in number of fine roots was observed only by some authors as a transitional response on exposure to low concentrations of O 3 shortly after initiation of the fumigation, while differences were not evident at the end of the experiment (Rantanen et al, 1994;Kasurinen et al, 1999;Andersen, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In Triticum aestivum, under high ozone levels, the quantity and quality of plants also deteriorated [4]. Several researchers reported that biomass in the mainstream plant was reduced under conditions of ozone stress [45,46]. Likewise, in Trifolium repens, the group treated with 120 ppb ozone had a 36% reduction in plant biomass in comparison to the control group, and Triticum aestivum was negatively impacted [39].…”
Section: Plant Growth Variables Affected By Ozone Concentration Treat...mentioning
confidence: 99%